ANALISIS RASIO KEMAMPUAN, KEMANDIRIAN DAN PERTUMBUHAN KEUANGAN DAERAH KOTA PEKANBARU - Hariati Eka Putri; Sri Endang Kornita; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the ratio of fanancial capacity, financial independence and financial growth of the Pekanbaru city years 2000-2014 as well as to view trends of financial capacity and financial independence of Pekanbaru years 2015-2020. This research is a quantitative descriptive study using analysis tools such as ratio and a polynomial trend. In the last fifteen years the average ratio of the financial capacity in Pekanbaru which is reflected in the ratio of Degree of Fiscal Autonomy (DOF) is still less, while the regional capability assessed in terms of expenditure as reflected in the Capability Index Routine relatively very less. While in terms of financial independence in Pekanbaru is still quite instructive, meaning that the central government's role is more dominant than the financial independence of Pekanbaru. When viewed from the ratio of growth is still likely to fluctuate with the average negative growth. Due to increased growth in the value of PAD, local revenue and expenditure is not routinely followed by construction spending growth.If the trend seen in 2015-2020 regional financial capability and financial independence of the region has a positive trend . That is projected in the coming six years the ratio of the degree of fiscal autonomy , the capability index ratio routine and financial independence ratio Pekanbaru is increasing every year .Keywords : Financial Capability , Financial Independence and Local Revenue